IMPROVEMENT ON FISHING JOB PERFORMANCE ON TUBING PUMP STUCK IN HEAVY OIL OPERATION THROUGH LEAN SIX SIGMA METHODOLOGY (A Case Study in Duri Field - PT. CDI) (The Indonesian Journal of Business Administration, 2020)
PT. Calgary Duri Indonesia (PT CDI – a disguised name) is a major Oil Company in Indonesia, PT CDI manages many fields which are located in around Duri City Riau Province. Every year Completion and Drilling (C&D) conducted 2000 workover jobs and 600 of them were conducted in Duri filed. 15% of that are related with tubing pump stuck. Most of production wells in Duri field are produced using sucker road pump. Road pumps become stuck due to buried by unconsolidated sand. There are several approaches to recover this stuck tubing pump, such as pulling out with high over pull, using surface jar, and conducting fishing job technic. During 2018 PT CDI spent US$ 2 Million dollars for conducting fishing tubing pump stuck and replace it with the new tubing pump. During this execution, team was experience with big nonproductive that adding unnecessary cost to the company. Company established and assigned a team to solve the problem through Lean Six Sigma. It uses systematic framework that comprise of five steps namely DMAIC (Define, Measure, Analyze, Improve, and Control). Project team performing Forum Group Discussion (FGD) to help project team during define, measure and analyze the problem including recommended the solutions.Team conducted improvement process in 4 steps; develop fishing handbook, improve SOP for wash pipe operation, Rig Schedule improvement and Contract Improvement. This process improvement was start in May 2019 and the last improvement was began in October 2019.During improvement phase the result are showing cycle time reduction and cost reduction. Cycle time was reduced from average 3.6 days/well become 3.1 days per well. Cost was reduced from US$ 28.6K/well to be US$27/Well. This project was implemented to the rest of program RLN-07 Through strong collaboration among team including and strong support from Business Partner, the project execution performance was improved significantly. The result of deployment in 27 wells, the cycle time was improved from average 3.6 days/well to 2.8 days/well and the cost reduced from average US$ 28.6K/well became US$ 24.9K/well. The Cpk of workover drilling cycle time was improved from 0.4848 to 1.3833 and Cpk for well cost was improved from 0.5904 to 1.1986 with sigma level higher than 5.5. As the result, the project team could save cost around $ 154K and potential to safe US$1 M. Keywords: Lean Six Sigma, Fishing Job, Cycle time, Well cost, SOP